Design Implication of a Distribution Transformer in Solar Power Plants Based on Its Harmonic Profile - Macías Ruiz, Iván Rafael; Trujillo Guajardo, Luis Alonso; Rodríguez Alfaro, Luis Humberto; Salinas Salinas, Fernando; Rodríguez Maldonado, Johnny; González Vázquez, Mario Alberto (Molecular Diversity Preservation International, 2021)
This article presents a comparative analysis for the design considerations for a solar power generation transformer. One of the main existing problems in transformer manufacturing is in the renewable energy field, specifically the solar power generation, where the transformer connected to the inverter is operated under a certain harmonic content and operating conditions. The operating conditions of the transformer connected to the inverter are particularly unknown for each solar power plant; thus, the transformer will be subject to a particular harmonic content, which is defined by the inverter of the solar power plant. First, the fundamental calculations for solar power plant transformer and the proposed methodology for the design calculation of the distribution pad-mounted three phase transformer are presented. Then, a design study case is described where a distribution transformer and an inverter of a particular solar power plant are used for the analysis. Next, the transformer under analysis is modeled using finite element analysis in ANSYS Maxwell® software, where the transformer will be designed for a non-harmonic and harmonic content application. Lastly, the main design parameters, flux density, the core losses and the winding excitation voltage of the transformer are calculated and presented in results and discussion section.